2008
DOI: 10.1002/ijc.23408
|View full text |Cite
|
Sign up to set email alerts
|

A high‐affinity human monoclonal antibody specific to the alternatively spliced EDA domain of fibronectin efficiently targets tumor neo‐vasculature in vivo

Abstract: The alternatively spliced extra-domain B of fibronectin is one of the best characterized markers of tumor angiogenesis. Similarly, the extra-domain A (EDA), which can also be inserted in the fibronectin transcript by a mechanism of alternative splicing, has been shown to preferentially accumulate around new blood vessels in certain tumors, but this antigen has not been investigated so far as a target for antibody-based biomolecular intervention. We here describe the generation of 3 human monoclonal antibodies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
316
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 225 publications
(326 citation statements)
references
References 58 publications
9
316
1
Order By: Relevance
“…The recombinant catalytic domain of CA IX was used for the isolation of human monoclonal antibodies from the ETH-2-Gold phage antibody library (Silacci et al, 2005). One of the clones isolated from the library ('A11') ( Table 1), which was shown to be non-inhibitory in the enzymatic assay described above (data not shown), was affinity-matured by combinatorial mutagenesis of residues in the CDR1 loops of VH and VL domains according to a procedure recently developed by our group (Villa et al, 2008), yielding clone A3. Additional mutagenesis of CDR2 loops led to the isolation of the daughter antibody clone CC7 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The recombinant catalytic domain of CA IX was used for the isolation of human monoclonal antibodies from the ETH-2-Gold phage antibody library (Silacci et al, 2005). One of the clones isolated from the library ('A11') ( Table 1), which was shown to be non-inhibitory in the enzymatic assay described above (data not shown), was affinity-matured by combinatorial mutagenesis of residues in the CDR1 loops of VH and VL domains according to a procedure recently developed by our group (Villa et al, 2008), yielding clone A3. Additional mutagenesis of CDR2 loops led to the isolation of the daughter antibody clone CC7 (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we have used antibodies in SIP format (Borsi et al, 2002;Villa et al, 2008), as this format and similar mini-antibody formats have extensively been shown to offer distinctive advantages both for imaging applications (Leyton et al, 2009);von Lukowicz et al, 2007;Wei et al, 2008) and for radioimmunotherapy of cancer (Berndorff et al, 2005;Tijink et al, 2006;Kenanova et al, 2007;Sauer et al, 2009). Recent publications suggest that smaller high-affinity ligands (MW o 2000 Da) may enjoy a much more rapid tissue distribution compared with antibodies and antibody fragments (Low et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Application of an optimized phage display selection protocol and subsequent screening methods resulted in the selection of scFvD2 showing a high affinity for FGFR1 with a low dissociation constant of 18 nmol/L. It is also worth noting that we subjected scFvD2 to affinity maturation by randomization of several residues located in the CDR1 of the heavy and light chains as described by others (39), but none of the resulted clones showed an improvement in the kinetic constants. It is likely that the amino acid motifs present in the CDR1 regions of the parental clone support the observed strong binding of scFvD2 to FGFR1.…”
Section: Discussionmentioning
confidence: 98%
“…The diversification of the CDR1 of both heavy and light chains was introduced as described by Villa and colleagues (39). An "off-rate" phage-selection strategy was applied to eliminate low affinity binders.…”
Section: Affinity Maturationmentioning
confidence: 99%